An Approach for Prediction of Diabetic disease by using b-Colouring Technique in Clustering Analysis - Lakshmi, Viji; Thilagavathi, K. (International Journal of Applied Mathematical Research, 2012)
Medical Data mining is the process of extorting hidden patterns from medical data. We propose the work which presents the development of clustering techniques for classifying Pima Indian diabetic database (PIDD). Here, clustering algorithm is used for predicting diabetic disease  based on graph b-coloring technique. The proposed technique presents a real representation of clusters by dominant objects that assures the inter cluster disparity in a partitioning and used to evaluate the quality of cluster.